Diagnostic performance of electrical cardiometry (ICON®) parameters in predicting fluid responsiveness in critically ill pediatric patients - Kurniawan Taufiq Kadafi; Rizki Dzakiyah Sholikhah, Wanda; Muhammad Reva Aditya; Saptadi Yuliarto; Charity Monica; Abdul Latief; Antonius Hocky Pudjiadi (Indonesian Pediatric Society, 2025)
Background Fluid resuscitation with appropriate and adequate amounts is very important in treating critically ill children, so reliable hemodynamic monitoring methods are needed to prevent fluid overload. Contractility index (ICON) is a novel, non-invasive index of left ventricular (LV) function, and contractility related to the electrical cardiometry device (ICON®). ICON® offers a non-invasive hemodynamic monitoring method to assess volume status, but its validity in predicting fluid response in the Indonesian pediatric population remains unknown. Objective To determine the diagnostic performance of ICON-derived parameters, especially change of cardiac output (ΔCO) and change in contractility index (ΔICON), in predicting fluid response, using change of stroke volume (ΔSV) as a reference standard. Methods A cross-sectional study was conducted in pediatric emergency and intensive care settings. Children aged 1 month to 18 years requiring fluid resuscitation were included. Hemodynamic parameters were measured using ICON® before and after a 10 mL/kg fluid bolus of crystalloid. Fluid responsiveness was defined as a >10% increase in ΔSV. Changes in parameters were analyzed using paired statistical tests. ROC analysis was used to assess the diagnostic accuracy of CO and ICON. Results Sixty-three subjects were analyzed. Significant median changes were observed after fluid bolus administration based on pre- and post-bolus comparison in change of heart rate (ΔHR: –8 bpm, P<0.001), change of systolic blood pressure (ΔSBP: +3 mmHg, P=0.042), change of diastolic blood pressure (ΔDBP: +2 mmHg, P=0.012), change of mean arterial pressure (ΔMAP: +0.67 mmHg, P=0.009). The ROC analysis showed that CO had the highest AUC (0.878), with a cut-off of 5.35%, sensitivity of 78.3%, and specificity of 87.2%. The ICON showed moderate accuracy (AUC 0.757), with a 0.45% cut-off, 69.6% sensitivity, and 71.8% specificity. Conclusion Electrical cardiometry (ICON®) demonstrated measurable changes in objective hemodynamic parameters following fluid bolus administration in critically ill children. Among ICON-derived parameters, a 5.35% increase in CO showed the best predictive performance for fluid responsiveness, while ICON showed moderate diagnostic value. These findings support the clinical utility of electrical cardiometry as a non-invasive tool to guide volume management in pediatric critical care.